Association between preoperative neutrophil-to-lymphocyte ratio and the survival outcomes of esophageal cancer patients underwent esophagectomy: a systematic review and meta-analysis - Wu, Xun; Liu, SiJie; Li, FengWei; Chen, YingTai (Frontiers in Oncology, 2024)
Objectives The purpose of this study was to assess the association between preoperative neutrophil-to-lymphocyte ratio (NLR) and the survival outcomes of esophageal cancer patients who underwent esophagectomy, the latest and comprehensive systematic review performed. Methods Related literature retrieved from PubMed, Web of Science, Embase, and Cochrane before January 2024, according to the inclusion criteria. Outcomes measured were overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), and cancer-specific survival (CSS). Results Eighteen studies with 6,119 esophageal cancer patients were retained for analysis. Meta-analysis demonstrated that OS (HR: 1.47; 95% CI: 1.29, 1.67; P < 0.00001), DFS (HR: 1.62; 95% CI: 1.29, 2.05; P < 0.0001), and CSS (HR: 1.62; 95% CI: 1.29, 2.05; P < 0.0001) were significantly shorter in the high NLR group compared with the low NLR group. In addition, meta-analysis revealed a similar RFS (HR: 1.47; 95% CI: 0.92, 2.35; P = 0.10) among the two groups. Subgroup analysis of OS and DFS based on mean/median age, NLR cutoff, and region found that all subgroups remained significant difference between two groups. Conclusion Among esophageal cancer patients who underwent esophagectomy, preoperative NLR can be used as prognostic factor independently. High-preoperative NLR is associated with poor prognosis. More large-scale, multicenter prospective clinical studies are needed to further validate the relationship between preoperative NLR and prognosis of esophageal cancer.